The Analysis of Student Responses to Matlab Applications in Physics Learning in High Schools - Kalsum, Umi; Fathurohman, Apit (Department of Physics Education, Universitas Mataram, 2023)
The development and presence of computer technology have made it easy for various parties to use it in life, including education, to support education. Physics is a branch of natural science. In learning physics, technology is needed in the learning process. One assistive software that can be used in learning physics is the Matrix Laboratory (MATLAB). This program can improve speed and accuracy in various calculations in learning. So that the time needed to work on it is more efficient and the results are better obtained more accurately than the calculations done manually. The purpose of this study was to describe and analyze students' responses to the application of MATLAB in physics learning. The data collection method used in this research is questionnaires with unstructured interview techniques assisted by the Google form application. The respondents used in the study were 10 class X students at UPT SMA Negeri 1 Ogan Komering Ilir. The results of data collection and analysis were descriptive and qualitative. The percentage of data obtained was analyzed using existing categories. The research results show that all aspects of the proportion of student responses are 83% with very good scores; this means that the MATLAB application is effectively used for learning physics.